Public views of health insurance in Japan during the era of attaining universal health coverage: a secondary analysis of an opinion poll on health insurance in 1967 - Ikuma Nozaki; Koji Wada; Osamu Utsunomiya (SAGE Publishing, 2017)
While Japan's success in achieving universal health insurance over a short period with controlled healthcare costs has been studied from various perspectives, that of beneficiaries have been overlooked. We conducted a secondary analysis of an opinion poll on health insurance in 1967, immediately after reaching universal coverage. We found that people continued to face a slight barrier to healthcare access (26.8% felt medical expenses were a heavy burden) and had high expectations for health insurance (60.5% were satisfied with insured medical services and 82.4% were willing to pay a premium). In our study, younger age, having children before school age, lower living standards, and the health insurance scheme were factors that were associated with a willingness to pay premiums. Involving high-income groups in public insurance is considered to be the key to ensuring universal coverage of social insurance.